Investigating Think Talk Write (TTW) Learning Model to Enhance Primary Students’ Writing Skill - Kurniaman, Otang; Yuliani, Titik; Mansur, Mansur (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
Bahasa Indonesia is one of the compulsory subjects taught in elementary school and important to be mastered because it aims for every student to communicate effectively and efficiently, both orally and in writing in accordance with the Indonesian rules is good and true. This study aims to investigeenhanging of 3rd grade primary students’ writing skill after implementation think talk write learning model in Bahasa Indonesia class. Research method in this study is experiment method. The research design used in this research is one-group pretest-posttest design, experimental research conducted in one group only without comparisongroup and the population subjects in this study were 35 students of 3rd grade elementary school in Pekanbaru. The result of this study is data of pretest and posttest, on the average pretest score of 60.94 with the category of skilled enough then on posttest increased to 75.67 with skilled category. Thus, it can be concluded that the think talk write learning model can influence the narrative writing skill of 3rd grade elementary school in Pekanbaru.